Solve the "w" variable in the equation.
First: set the equation to equal "0" - subtract 5 from both sides (when you move a term to the opposite side, always use the opposite sign).
w^3 + 5w^2 - w - 5 = 5 - 5
w^3 + 5w^2 - w - 5 = 0
Sec: with 4 terms, group "like" terms & factor both sets of parenthesis.
(w^3 - w) + (5w^2 - 5) = 0
w(w^2-1) + 5(w^2-1) = 0
(w^2-1)(w+5) = 0
Third: solve the "w" variables - set both parenthesis to "0"
a. w^2 - 1 = 0
* Add 1 with both sides.
w^2 - 1 + 1 = 0 +1
w^2 = 1
*Eliminate the exponent - find the square root of both sides.
V`(w^2) = +/- V`1
w = +/- 1
w = 1, -1
b. w+5 = 0
*Subtract 5 from both sides.
w+5 -5 = 0 - 5
w = 0 - 5
w = - 5
Solutions: 1, - 1, -5
2007-04-12 17:16:28
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
2⤊
1⤋
Ok, so you have w^3 + 5w^2 - w = 5
First you need to set it equal to 0 by moving the 5 over to the other side of the equation, giving you:
w^3 + 5w^2 - w - 5 = 0
This can be simplified basically by a guess and check type of thing.
Let's choose a factor, say (x + 5) and see if it fits, we will have to use synthetic division:
-5 | 1 5 -1 -5
1 -5 0 5
1 0 -1 0
This turns out to say this:
w^2 - 1
So now we have two factors, (w + 5) and (w^2 -1)
(w + 5)(w^2 - 1) = 0
w^2 - 1 is a difference of squares so it simplifies even further:
(w + 5)(w + 1)(w - 1) = 0
So the solutions are as follows:
w = -5
w = -1
w = 1
And there you go.
2007-04-12 16:34:32
·
answer #2
·
answered by Eolian 4
·
1⤊
0⤋
w3+5w2-w-5=0 You can factorize it as
(x-1)( x2+6x+5) and the second factor is (x+5)(x+1) So the roots are
x=1 x=-1 and x=-5
2007-04-12 16:29:26
·
answer #3
·
answered by santmann2002 7
·
1⤊
0⤋
w= -5 w= -1 w= 1; since it is w^3 you know there has to be three answers
2007-04-12 16:28:50
·
answer #4
·
answered by purple122988 2
·
0⤊
2⤋
abc method
2007-04-12 16:27:08
·
answer #5
·
answered by Anonymous
·
0⤊
2⤋